2022
DOI: 10.1039/d2ra04254a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bacillus cereus LV-1 on the crystallization and polymorphs of calcium carbonate

Abstract: The study of CaCO3 polymorphism is of great significance for understanding the mechanism of bacterial carbonate mineralization and the genesis of carbonate rock formation throughout geological history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Tobler et al showed that an increase in pH contributes to the stabilization of ACC, slowing down the crystallization process and the passage of the vaterite phase in which ACC crystallizes into calcite [30]. In a bacterial environment, the polymorphic transition of CaCO 3 takes many hours and occurs at significantly lower pH values (about 7.5 [16,31]). Such stabilization may be explained by the presence of organic inclusions (polysaccharides, eDNA or amyloids) in the extracellular matrix, since the stabilizing role of some macromolecules such as polyaspartic acid, polyethylene glycol and dendrimers was demonstrated in the in vitro system [32], as was stabilization by protein structures for the system in vivo [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobler et al showed that an increase in pH contributes to the stabilization of ACC, slowing down the crystallization process and the passage of the vaterite phase in which ACC crystallizes into calcite [30]. In a bacterial environment, the polymorphic transition of CaCO 3 takes many hours and occurs at significantly lower pH values (about 7.5 [16,31]). Such stabilization may be explained by the presence of organic inclusions (polysaccharides, eDNA or amyloids) in the extracellular matrix, since the stabilizing role of some macromolecules such as polyaspartic acid, polyethylene glycol and dendrimers was demonstrated in the in vitro system [32], as was stabilization by protein structures for the system in vivo [33].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studies of the nano-and meso-sized structures of polymorphs formed during calcium carbonate crystallization or polymorphic transitions in a system containing bacterial cells. However, there are a large number of publications in which the chemical composition of precipitates formed during biomineralization process was characterized by various methods, mainly IR spectroscopy [35][36][37], XRD [31,[34][35][36][37][38], SEM, FIB and EDX [31,34]. The above methods were frequently used to describe the morphology [31,34,36] and polymorphic composition of crystals [31,[34][35][36]), which varied in different types of bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation